STORY ARCHITECTURAL FORMS (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
Architectural images express the ideas of society in the language of geometric, abstract forms, therefore it is necessary to correlate architectural form with the corresponding content indirectly, following the principle of the historicity of the created images. Seemingly different buildings can have very subtle connections, preserving a somewhat constant figurative structure, and first of all - symbolic. Architectural forms created by people and for people were a reflection of the worldview system of the era.